KEY DRIVERS INFLUENCING GREEN BUILDING PERFORMANCE WITHIN THE CONSTRUCTION INDUSTRY IN UAE - ALBLOOSHI, EIMAN MOHAMMED GHAREEB ABDULLA (2018)
This research sought to investigate the key drivers influencing the performance of Green Building (GB) in the UAE construction industry and whether these drivers are being changed over time or not. A quantitative research was executed using the survey methodology with stakeholders in various industry roles including consultants, contractors, and clients among others drawn from government, semi-government, and private organizations. The findings show that readiness in GB understanding was high among consultants, contractors, master developers, clients, researchers, and learners and that GB attributes were well developed in GB codes including ventilation and air quality, building fabric and systems, generation and renewable system, water efficient fittings, microclimate and outdoor comfort, neighborhood pollution, access and mobility, thermal comfort, environmental impact assessment, and hazards materials. The financial, operational, functional, environmental, and management drivers were reported to be important in GB adoption in the UAE. The results also indicated that the general requirements, Bronze Sa’fa requirements, Silver Sa’fa Requirements, Gold Sa’fa Requirements, and Platinum Sa’fa Requirements of the Al Sa’fat evaluation system have been remarkably implemented in the UAE.